THE DESCRIPTION OF ENGLISH TEACHING STRATEGY USED IN TEACHING READING IN ISLAMIC SENIOR HIGH SCCHOOL: Teaching Strategy - Lailatul Masruroh masruroh (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2022)
This research is talked about descriptive qualitative, this research was done to know the teaching strategy in teaching English. This research was want to answer the question How is the teaching strategy in teaching reading in MA Maarif , and the objective was to describe the teaching strategy in teaching reading. To describe the answer the researcher used three instruments for taking the data, they are observation and questionnaire. Finding, the teacher applied those strategies. From the first to the third meeting, the teacher applied the different strategies. At the first and second, the teacher applied the discovery learning strategy where the learning materials were searched and found by the students themselves through various activities, and the third meeting the teacher used question answer strategy and discussion strategy.